2010
DOI: 10.4103/0972-124x.76921
|View full text |Cite
|
Sign up to set email alerts
|

Viability of bacteria in dental calculus - A microbiological study

Abstract: Aim:The aim of this study was (1) To investigate the viability of bacteria within supragingival and subgingival calculus, (2) To examine motility of bacteria, and (3) To identify bacterial morphotypes in calculus.Materials and Methods:Supra and subgingival calculus were harvested from 30 subjects having clinical evidence of chronic inflammatory periodontal disease and were divided into two groups. Samples from both groups were immediately transported to the Department of Microbiology for gram staining, acridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Transmission electron microscopic and bacterial culture studies on calculus by Sidaway DA, 24 Friskopp J et al, 25 Tan BT et al, 7 Moolya NN et al 9 have proved the presence of intact and viable bacteria within the non-mineralized channels, islands and lacunae in supragingival and subgingival calculus. Thus, calculus may serve as a reservoir of viable microorganisms and play a crucial role in the etiology and recurrence of oral infections even after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission electron microscopic and bacterial culture studies on calculus by Sidaway DA, 24 Friskopp J et al, 25 Tan BT et al, 7 Moolya NN et al 9 have proved the presence of intact and viable bacteria within the non-mineralized channels, islands and lacunae in supragingival and subgingival calculus. Thus, calculus may serve as a reservoir of viable microorganisms and play a crucial role in the etiology and recurrence of oral infections even after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies evaluating the bacterial presence and viability in calculus, or studies assessing the influence of salivary urea as well as pH on dental calculus have been reported in the literature. 7 , 8 , 9 , 10 To the best of our knowledge, this is the first time that a study has been attempted evaluating the clinical, biochemical and microbiological parameters with the aim to explore the influence of salivary urea, pH and ureolytic bacteria on the formation of dental calculus and periodontal status in patients with good, fair and poor oral hygiene. The objectives were to assess the levels of salivary pH, urea and determine its influence on calculus formation and periodontal status; to identify and quantify the amount of ureolytic bacteria within dental calculus using gram-staining, bacterial culture and biochemical reactions and determine a possible correlation between salivary urea and ureolytic bacteria within dental calculus.…”
Section: Introductionmentioning
confidence: 99%
“…The rough surface and porous structure of calculus provide an ideal substrate for bacterial colonization and serve as a reservoir for toxic bacterial components and antigen [ 6 ]. Moreover, studies have identified viable bacteria within supra- and subgingival calculus, including Porphyromonas gingivalis , Treponema denticola , and Aggregatibacter actinomycetemcomitans [ 7 – 9 ]. Calcifying nanoparticles, the calcified self-propagating entities that are found in dental calculus may contribute to the formation of calculus and pathogenic calcification of epithelial cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calculus, having a rough surface and porous structure, is an ideal substrate for bacterial colonization and serve as a reservoir for toxic bacterial components and antigen [6] . Porphyromonas gingivalis, Treponema denticola, and Aggregatibacter actinomycetemcomitans have been identified within supra-and subgingival calculus [7][8][9] . Calcifying nanoparticles are found in dental plaque may contribute to the formation of calculus and pathogenic calcification of epithelial cells [10] .…”
Section: Introductionmentioning
confidence: 99%